Meis1 regulates the metabolic phenotype and oxidant defense of hematopoietic stem cells - Kocabas, Fatih (American Society of Hematology, 2012)
The role of Meis1 in leukemia is well established, but its role in hematopoietic stem cells (HSCs) remains poorly understood. Previously, we showed that HSCs use glycolytic metabolism to meet their energy demands. However, the mechanism of regulation of HSC metabolism, and the importance of maintaining this distinct metabolic phenotype on HSC function has not been determined. More importantly, the primary function of Meis1 in HSCs remains unknown. Here, we examined the effect of loss of Meis1 on HSC function and metabolism. Inducible Meis1 deletion in adult mouse HSCs resulted in loss of HSC quiescence, and failure of bone marrow repopulation after transplantation. While we previously showed that Meis1 regulates Hif-1α transcription in vitro, we demonstrate here that loss of Meis1 results in down-regulation of both Hif-1α and Hif-2α in HSCs. This resulted in a shift to mitochondrial metabolism, increased reactive oxygen species production, and apoptosis of HSCs. Finally, we demonstrate that the effect of Meis1 knockout on HSCs is entirely mediated through reactive oxygen species where treatment of the Meis1 knockout mice with the scavenger N-acetylcystein restored HSC quiescence and rescued HSC function. These results uncover an important transcriptional network that regulates metabolism, oxidant defense, and maintenance of HSCs.